PENGARUH ASIMETRI INFORMASI, KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL PADA MANAJEMEN LABA - Dwijayanti, Ni Made Apsari; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2017)
Earnings information is an important factor in measuring the performance of management and assist owners and other parties interested in the company to do an assessment on earning power in the future. The purpose of this study was to determine the effect of information asymmetry, managerial ownership and institutional ownership to earning management. This research was conducted at all manufacturing companies in Indonesia Stock Exchange 2009-2013 period. The samples used as many as 35 companies from the population of 123 companies, through a purposive sampling method. The data collection is done by using the method of observation nonparticipant through the financial statements. The analysis technique applied is a technique of multiple linear regression analysis. The results show positive effect of information asymmetry on earnings management, managerial ownership and institutional ownership has a negative effect on earnings management.
Keywords: Asymmetry of Information, Managerial Ownership, Institutional Ownership, Earnings Management .